Potentiella arealer för ökad virkesproduktion i norra Sverige genom skogsodling med Pinus contorta var. latifolia, Larix sukaczewii, Abies lasiocarpa, Populus × wettsteinii och Picea mariana - Söderholm, Erik; Öhman , Mikael (SLU/Dept. of Forest Ecology and Management, 2010)
Sweden is a country with few native tree species. According to Govt. 2007/08: 108, exotic tree species may be seen as an opportunity to increase the growth of tree volume in Sweden. Potential areas where explored In this work for cultivation with Pinus contorta var. latifolia Engelm., Larix sukaczewii Dylis, Abies lasiocarpa (Hook.) Nutt., Populus × wettsteinii Hämet-Ahti (tremula x tremuloides) and Picea mariana (Mill.) Britton et.al. for increased volume growth per hectare in northern Sweden. Yield experiments indicated that these trees can outperform our native trees in volume growth on some locations. Those areas were found with the help of several maps and models. The models only took in account the abiotic factors that play a major role for the selected trees competitiveness in volume growth against our native tree species. The work resulted in several maps showing the potential area for each tree species and one in which all the five species were included. Where several species fits on the same area were primarily P. contorta var. latifolia chosen, and then L. sukaczewii, P. mariana, P. × wettsteinii and last A. lasiocarpa. The results show that cultivation with P. contorta var. latifolia to increase timber production can be possible on 6.45 million hectares, L. sukaczewii on 2.9 million hectares, A. lasiocarpa on 2.64 million hectares, P. × wettsteinii on about 40 500 hectares and P. mariana on 4 200 hectares. Overall 58 % or about 10 million hectares of the productive forest in north Sweden could be possible for cultivation to increase volume growth with P. contorta var. latifolia, L. sukaczewii, A. lasiocarpa, P. × wettsteinii and P. mariana. Additional 1.3 million hectares consisting of mainly mountain/montane areas and agricultural areas can be cultivated with Populus × wettsteinii and Abies lasiocarpa for increased yield. On forest land in northern Sweden the distribution in percent after merging was 43 % P. controta 42 % other indigenous species 12 % L sukaczewii and 3 % A. lasiocarpa. P. × ...